Evaluation of Web-Based Car Park Information System at PPPSRS Puri Casablanca Jakarta - Sanusi, Beno Aditya; Herlawati, Herlawati; Kustanto, Prio; Harviansyah, Muhammad; Yana, Anisa Feby; Kurniawan, Ervan Dwi (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2021)
Problems in conventional and manual parking are the inability to obtain complete, informative, and interactive parking information because the manual system cannot provide complete parking information. Information technology can be implemented in a parking system to help provide more accurate, fast, and easily accessible information. In addition, the parking system interface can be made user-friendly, hence, the parking attendants can operate it properly. This parking system uses a client-server model with a shared database. The author found problems in the car parking system at PPPSRS Puri Casablanca Jakarta, i.e. still using the previous version of XAMPP. The research methodology used in this study are: Observation Methods, Literature Methods, and Interview Methods. The proposed Car Parking application showed acceptable for use by parking attendants of PPPSRS Puri Casablanca Apartment Jakarta. The menu choices presented are sufficient and the web design is simple so it doesn't confuse the parking attendant.